PENGARUH KEMAJUAN TEKNOLOGI TERHADAP VOLUME PEJUALAN RITEL DI KOTA MOJOKERTO - Rachmad Sholeh; Khasbulloh Huda (Universitas Tribhuwana Tunggadewi, 2020)
The development of the business world today is increasingly diverse and competitive, the pace of development is very difficult to predict, so having the right strategy is the key for a company to continue to compete and survive. Along with technological advancements and the development of communication suggestions, the company is utilizing these technological advances as a marketing strategy tool to promote its products. Given the growth of buying and selling transactions in the network or online in Indonesia at this time is very rapid, with this being used by companies to market and promote via the internet. This study aims to determine the effect of the implementation of technological progress on retail sales volumes. The development of information technology that is growing very rapidly now influences the community in supporting various business activities both large and small so that it can be known globally. The most obvious impact is that besides being known, it can also increase sales volume. Digital Marketing is one of the very large marketing media that has an influence. Using digital marketing in this case is social media and E-commerce. The most widely used social media is Facebook, Twitter and Instagram. The subjects in this study were retail owners, managers, and employees who were selected by purpose sampling.